Measuring New Learners' Adaptability and Psychological Health: Using School Wellbeing's Intervening Role at Islamic Boarding Schools - Mohammad Zaini (Academia Publication, 2025)
The study aims to test the adaptability to psychological well-being through the role of the intervening variable, school well-being at Miftahul Ulum Islamic Boarding School, Lumajang Regency. The study's limitations include its emphasis on three variables, which could restrict its depth of understanding. Furthermore, data collecting using a single-location sample. This research is quantitative with an associative approach. The population in this study was new students at Miftahul Ulum Lumajang Islamic boarding school, with a purposive sampling technique using the Slovin formula of 102 new students. Data collection in this study used a questionnaire/questionnaire via Google Form. The data processing techniques used in this study used the SMART-PLS version 4.0 application. The research findings in the hypothesis testing concluded: 1) adaptability has a significant positive effect on the psychological well-being of new students by 22.3%, 2) adaptability has a significant positive effect on the school well-being of new students, by 69.1%, 3) school well-being has a significant positive effect on the psychological well-being of new students by 60.5%, 4) adaptability has a significant positive effect on the psychological well-being of new students through the intervening role of school well-being variables by 41.8%.